Satisfaction and quality of care in prenatal check-ups at the obstetrics department of a public health center in Lima - Delgado-Meneses, Sindy Mabel (2025)
Objetive: To identify the relationship between satisfaction and quality of care in prenatal care at a state health center in Lima. Methods: The sample consisted of 100 pregnant women who attended prenatal care at a state health center in Lima over a 4-month period. This study was observational, descriptive, and cross-sectional, with a quantitative and correlational approach. It was a relational level study, as its objective was to determine the relationship between the independent and dependent variables and identify whether there is an association between them. To this end, two questionnaires were used: one to measure the satisfaction variable and another to evaluate the quality of care variable. Results: The results showed a statistically significant relationship between satisfaction and quality of care in prenatal care at a state health center in Lima. The contingency coefficient C = 0.692 and a p value < 0.05. Conclusion: that oregano oil does have an antifungal effect against Candida albicans.